2022
DOI: 10.1021/acs.joc.2c00700
|View full text |Cite
|
Sign up to set email alerts
|

TEMPO-Promoted Mono- and Bisimidation of Tertiary Anilines: Synthesis of Symmetric and Unsymmetric N-Mannich Bases

Abstract: A TEMPO-promoted method was developed for the synthesis of symmetric bis-N-Mannich bases via sequential activation of two α,α′-amino C(sp 3 )−H bonds of N,N-dimethylanilines under mild conditions. This methodology was further extended for monoimidation of α-amino-functionalized methylanilines to give unsymmetric N-Mannich bases in good to high yields. Several control experiments were performed, and the coupling reaction outcomes indicated that the oxoammonium (TEMPO + ) species is involved in the reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 49 publications
1
3
0
Order By: Relevance
“…On the basis of these experimental results and our earlier work, [35,36] a tentative mechanism for this coupling reaction is depicted in Scheme 6. Initially, the tertiary amine is activated by NIS to generate the iminium ion intermediate A, while succinimide (NHS) is liberated.…”
Section: Resultssupporting
confidence: 60%
See 1 more Smart Citation
“…On the basis of these experimental results and our earlier work, [35,36] a tentative mechanism for this coupling reaction is depicted in Scheme 6. Initially, the tertiary amine is activated by NIS to generate the iminium ion intermediate A, while succinimide (NHS) is liberated.…”
Section: Resultssupporting
confidence: 60%
“…Recently, we have developed CÀ N cross-coupling approaches of tertiary amines to form N-Mannich bases using N-halosuccinimide (NXS) [35] or NXS/TEMPO. [36] Mechanistic studies showed that NXS mediated CÀ H bond activation occurs via an ionic pathway, and that the active iminium cation is formed during the reaction. Inspired by this result, we envisioned that the iminium cation might be trapped by a carbon-based nucleophile to achieve a CÀ C cross-coupling reaction, in which the CÀ N coupling adduct (N-Mannich base) might provide a stabilizing effect like an "iminium ion reservoir".…”
Section: Introductionmentioning
confidence: 99%
“…As examples, electron-rich alkenes can add to the intermediate iminium ion and the formed carbenium ion is trapped by the carbonyl O atom of the N-carbamate protecting group (e.g., Boc), 662 resulting after O-dealkylation in an oxidative annulation 672 of the isoquinoline (Scheme 26a). Amides can act as internal nucleophiles 673 in an enantioselective cyclization in the presence of chiral phosphoric acids (Scheme 26b). 663,674 Further, the iminium ion trapping with cyanide (Scheme 26c), 664,675 azide (Scheme 26h), 669 an allyl silane (Scheme 26d), 665 and alkynes (Scheme 26e and 26g) 666,668,676 was reported.…”
Section: Physical Properties and Reactivitymentioning
confidence: 99%
“…Recently, we reported the iron catalyzed oxidative amidation of tertiary amines using molecular oxygen as the terminal oxidant [25]. Based on our previous work on the oxidative functionalization of tertiary amines [26] and our ongoing research interests in this field, herein, we report a simple protocol for the FeCl 3 catalyzed “synthesis of pyrrolo[2,1‐ a ]isoquinolines” under mild conditions (Scheme 1e).…”
Section: Introductionmentioning
confidence: 99%